2021
DOI: 10.1371/journal.pone.0260612
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised feature learning for electrocardiogram data using the convolutional variational autoencoder

Abstract: Most existing electrocardiogram (ECG) feature extraction methods rely on rule-based approaches. It is difficult to manually define all ECG features. We propose an unsupervised feature learning method using a convolutional variational autoencoder (CVAE) that can extract ECG features with unlabeled data. We used 596,000 ECG samples from 1,278 patients archived in biosignal databases from intensive care units to train the CVAE. Three external datasets were used for feature validation using two approaches. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…3,5,10,24 Other studies investigated the use (variational) auto-encoders 12-lead ECGs in smaller and showed that VAEs can be useful for compression of ECGs, data augmentation, clustering, and feature generation. [25][26][27][28] Interestingly, Kuznetsov et al 28 also deterthat factors are needed to encode a single or beat Our work makes the latent space of a VAE (i.e. FactorECG) clinically useful and explainable to physicians, by linking the ECG factors with known ECG measurements and diagnostic statements (Figures 4 and Tables 2 and 3), (ii) providing sive visualizations offline (Figure 2) and using an tool (https:// decoder.ecgx.ai), and (iii) showing that the ECG factors have equate predictive power in various downstream tasks.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10,24 Other studies investigated the use (variational) auto-encoders 12-lead ECGs in smaller and showed that VAEs can be useful for compression of ECGs, data augmentation, clustering, and feature generation. [25][26][27][28] Interestingly, Kuznetsov et al 28 also deterthat factors are needed to encode a single or beat Our work makes the latent space of a VAE (i.e. FactorECG) clinically useful and explainable to physicians, by linking the ECG factors with known ECG measurements and diagnostic statements (Figures 4 and Tables 2 and 3), (ii) providing sive visualizations offline (Figure 2) and using an tool (https:// decoder.ecgx.ai), and (iii) showing that the ECG factors have equate predictive power in various downstream tasks.…”
Section: Discussionmentioning
confidence: 99%
“…NNs have already been implemented in medicine and used in various studies in the fields of radiology, cardiology, neurology, and pathology [30][31][32][33][34]. But several caveats prevent such techniques from being widely used.…”
Section: Discussionmentioning
confidence: 99%
“…One unsupervised technique is the Convolutional Autoencoder (CAE), which is trained with unlabelled data [29,30]. Such NNs were developed to work with high-dimensional data and have already been implemented to solve medical problems, such as radiology, cardiology, neurology, and even pathology [30][31][32][33][34]. In brief, the input layer of the CAE compresses the data and creates a code, which is then used to reconstruct them in the output layer [30].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al 313 . deployed a Convolutional Variational Autoencoder (CVAE) for unsupervised ECG feature learning from an expansive collection of 596,000 samples.…”
Section: Machine Learning (Ml) Methods In Clinical Databasesmentioning
confidence: 99%
“…innovated an "autoencoder feature selector" by melding autoencoder and group lasso regression, targeting the extraction of salient linear and nonlinear data features. Jang et al313 deployed a Convolutional Variational Autoencoder (CVAE) for unsupervised ECG feature learning from an expansive collection of 596,000 samples. This method astutely captures vital clinical attributes from the Asian University Medical Center's ICU patients, even without annotations.…”
mentioning
confidence: 99%